Investigating the Impact of Waste Management Awareness and Community Participation on the Perceived Effectiveness of Solid Waste Management - Bansal, Shilpi; Singh, Nishma; Yadav, Kalpna; Kumari, Saroj; Agarwal, Renu; Sharma, Gunjan (Journal of Neonatal Surgery, 2025)
Aim of the Study Proper management practices of solid waste matter since they protect environmental health and public welfare and promote resource-saving efficiency. The research project examines the relationship between waste management understanding and waste management perception and environmental understanding and community activities on citizens' solid waste management effectiveness beliefs. Methodology A structured questionnaire survey obtained data from 443 participants who underwent statistical correlation testing and regression analysis and ANOVA analysis. Results The research data demonstrates that waste management understanding and waste management attitudes have substantial influence on solid waste management effectiveness yet environmental issue perception remains significant but has less impact. The combination of community participation along with citizen-authority collaboration creates outcomes that lead to better waste management. This research proved that educational programs did not lead to significant results which ended the theory that knowledge growth alone could achieve efficient waste management practices. Originality The study expands understanding in this field because it establishes essential waste management performance indicators which show public education reinforced by positive attitudes and community actions lead to sustainable outcomes.